Identification of Secondary Metabolites from Zingiber officinale as Inhibitors for Keap 1-Nrf2 small Molecules through Molecular Docking Techniques - Nivedha Sukumar (International Journal of Bioinformatics and Computational Biology, 2023)
Objective: Therapeutic plants aid in treating cancer-based cell signaling pathways and preventing certain risk factors. Zingiber officinale has a variety of anti-inflammatory characteristics also contributing to enhanced immunity, reducing cancer risk and used to target the KEAP NRF2. When overexpressed in response to oxidative stress and DNA damage, elevates the risk of developing multiple cancers. NRF2 cellular sensors, which also control and coordinate their expression aid in defending healthy cells against carcinogens. Methods: The approach employed to accomplish this was the individual assessment of each of the 50 phytochemicals from Zingiber officinale's binding affinity for our target protein, KEAP1 NRF2. PyRx, a software programme that allows to dock the top ligands with best binding affinity and the target protein, served as the molecular docking platform for the study. In further process of the investigation, BIOVIA was used to retrieve the 3D and 2D structure of each ligand and the Protein structure retrieved from PUBsum. Along with this, the ligands bound to the target protein in PYMOL. The 8 ligands were sent for ADMET filters. Results: Molecular docking resulted in Gingerglycolipid A, B, C, Gingernone A,B, Cyclosalivene, viridiflourine, and Isogingernone B as the top 8 ligands with appropriate binding affinity. The ADMET lab analysis resulted in the Cyclosalivene and viridiflourine along with Gingerglycolipid A, B,C inhibiting against Keap1-Nrf2 small molecules or its pathway. Further progression of targeting this protein using ginger. Conclusion: These phytocompounds can help in the further suppression and the progression of the KEAP1 NRF2 protein and pathway to result in any human diseases or carcinogen activation due to Oxidative stress.
Keywords: ADMET lab; ARE mediated pathway; Cancer; Ginger; Keap1-NRF2 pathway; NRF2-sMAF; Oxidative stress; Phytocompound; molecular docking